A school support experience in pandemic context through the voices of participants - Agustina Angriman, María (2024)
This article describes the main characteristics and the impact in the community of a school support program led by university students during the COVID-19 pandemic. This study recovers the voices of the people involved in the university volunteer program: undergraduate students, children and families. The program was developed in a primary health center dependent of a private University in Buenos Aires, Argentina. The health center provides integral attention to underprivileged families. COVID-19 pandemic has exacerbated the inadequate living conditions and affected the possibilities of the educationalcontinuity in children (Tuñón, 2021). The school support program´s aim was to guide children´s learnings in a personalized way. The analysis of the surveys completed by the university students who led the program and the workshops with children and their families reveals that the participation in the programimplies benefits in different areas. University students recognized the development of abilities. Childrenidentified learning about specific content related to the primary level curriculum. Families identified theprogram has provided them support in their parenting role. In conclusion, the school support programencourages meaningful learning in the participants involved.